TENGKU BESAR SAYID SAGAF SEBAGAI RAGENT DI KERAJAAN SIAK 1908-1915 - Hidayat, Fahril; Tugiman, Tugiman; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was (1) to find out the condition of the Siak Kingdom before Tengku Besar became Ragent. (2) to find out the condition of the Siak Kingdom during the Tengku Besar became Ragent. (3) to find out the end of Tengku Besar's tenure as a Ragent in the Siak Kingdom. Siak Kingdom is a Malay patterned kingdom which was founded in 1723 in Buantan with its first king, Raja Kecik, who was the son of Mahmud Syah II. The kingdom of Siak is led by twelve Sultan and one Ragent. This scientific paper will discuss the Tengku Besar Sayid Sagaf. Tengku Besar Sayid Sagaf is a Ragent in the Siak Kingdom. Tengku Besar Sayid Sagaf became Ragent in the Kingdom of Siak in 1908-1915. Tengku Besar is a cousin of Sultan Syarif Qasyim II. The research method used in this study is the interview method and literature review. The general results of the study, Tengku Besar Sayid Sagaf, became Ragent in the Siak Kingdom because Sultan Syarif Qasyim II was studying in Batavia. Tengku Besar Sayid Sagaf is a cousin of Sultan Syarif Qasyim II.Key Words: Tengku Besar Sayid Sagaf, Ragent, Siak Kingdom